Essentialism vs. social constructionism in the study of human sexuality - DeLamater, John D.; Hyde, Janet Shibley (The Journal of Sex Research, 1998)
According to classical essentialism, there are underlying true forms or essences, there is discontinuity between different forms rather than continuous variation, and these true forms are constant over time. Modern essentialism consists of a belief that certain phenomena are natural, inevitable, and biologically determined. We consider sociobiology, evolutionary psychology, genetic research, brain research, and endocrine research as examples of essentialist approaches, focusing particularly on how these research approaches treat sexual orientation and sexual attraction. Social constructionism, in contrast, rests on the belief that reality is socially constructed and emphasizes language as an important means by which we interpret experience. We briefly review social constructionist research on sexual orientation and sexual attraction. Finally, we review examples of conjoint or interactionist research, uniting biological and social influences. We conclude that, although there may be theories and research that conjoin biological and social influences, there can be no true conjoining of essentialism and social constructionism.
Keywords: approches et analyses; comparaison; construction sociale; cours; discipline; essentialisme; histoire et politique; méthodologie; postmodernisme; premier cycle; sciences humaines; sex2283; sociologie; thématiques

Le projet féministe à l’aube du XXIe siècle : un projet de libération et de solidarité qui fait toujours sens - Descarries, Francine (Cahiers de recherche sociologique, 1998)
En situant les rapports de genre au cœur de leur élaboration conceptuelle et en inscrivant leur transformation comme un enjeu stratégique, les études féministes se sont progressivement imposées dans l'univers des sciences humaines comme une approche critique et comme une problématique du changement. Après une revue des trois grands courants de pensée qui se sont développés au sein et en marge du mouvement féministe au cours des dernières décennies, l'auteure se demande si la pensée féministe, ou plutôt les différents courants de la pensée féministe actuelle sont encore engagés dans ces mêmes fins. Sont-elles encore capables de contribuer au renouvellement des savoirs, de proposer un projet de société original, et d'imaginer les termes d'un nouveau contrat entre les genres ? Sont-elles capables de nourrir une lutte féministe unie, une politique de coalition ouverte à la diversité et à la différence, mais qui ne perd rien de sa cohésion et de sa force de ralliement ? Ces questions servent de pistes thématiques pour la discussion de l'auteur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; approches et analyses; cours; discipline; fem1000; féminisme matérialiste; histoire et politique; justice sociale; militance; mouvements des femmes*; mouvements féministes; occident; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociologie; thématiques

L’économie politique du sexe : transactions sur les femmes et systèmes de sexe/genre - Rubin, Gayle (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 1998)
La littérature sur les femmes — tant féministe qu’antiféministe — est une longue rumination quant à la nature et à la genèse de leur oppression et de leur subordination sociale. La question n’est pas sans importance, car les réponses qui lui sont données déterminent la manière dont nous envisageons l’avenir et si nous jugeons réaliste ou non d’espérer une société égalitaire entre les sexes. Plus important, l’analyse des causes de l’oppression des femmes fonde toute estimation de ce qu’il faudrait exactement changer pour réaliser une société sans hiérarchie de genre
Keywords: 1900-1999; 1960-1969; 1970-1979; anthropologie; approches et analyses; capitalisme; classe ouvrière; cours; discipline; europe; famille; fem1000; france; féminisme matérialiste; histoire et politique; inégalités; marxisme; patriarcat; premier cycle; psychanalyse; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences; sciences humaines; soc1016; soc2014; sociologie; systèmes d'oppressions; thématiques; théories féministes

Lessons from the damned: queers, whores, and junkies respond to AIDS - Stoller, Nancy E. (Routledge, 1998)
"Lessons from the Damned challenges the notion that public health theories and official organizations have the greatest impact on the fight against AIDS. Instead, Stoller looks closely at the ways the most disenfranchised - the poor, people of color, drug users, gay men and lesbians, and women - have built social movements to fight the epidemic. Drawing upon extensive ethnographic research and the words of the activists themselves, as well as the literature of social movements and theories of bureaucracy, Stoller offers guidelines for dealing with diversity and conflict and also with both theoretical and practical perspectives on cross-community and international organizing."--BOOK JACKET.
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; capitalisme; care; cours; discipline; histoire et politique; hétérosexisme; justice sociale; militance; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; sida; soc2014; sociologie; sofia; systèmes d'oppressions; thématiques; états-unis